Visual Support Based on Indonesian Local Wisdom for Personal Hygiene Learning of Children with Autism Spectrum Disorders - Ardianingsih, Febrita; Ashar, Muhammad Nurul; Budiyanto, Budiyanto (Journal of Education for Sustainability and Diversity, 2023)
The degree of severity of autism can cause deficits in the development of activities of daily living, one of which is personal hygiene skills (bathing, toileting, washing hands, brushing teeth). The development of personal hygiene skills is important for children with autism spectrum disorders for health promotion and ensuring opportunities for increased socialization and participation in various environments. Strategies that incorporate visual support are considered evidence-based practices that capitalize on the strengths of children with ASD. Sources of images for creating visual support are actually quite a lot available on the internet, but they are still rarely suitable for Indonesian culture. This study aims to (1) develop visual support products based on local wisdom as a personal hygiene learning strategy for children on the autistic spectrum, and (2) determine the feasibility of visual support products based on local wisdom in learning personal hygiene for children with autism spectrum disorders. This study adapted the ADDIE approach to only 3 stages: Analyze, Design, and Develop. The findings of this study are: (1) this development resulted in an electronic catalog book and visual supports on personal hygiene based on Indonesian local wisdom, and (2) the electronic catalog book and visual supports based on Indonesian local wisdom in learning personal hygiene for children with autism spectrum disorders are very feasible based on expert validation.